Exploring the Potentials and Barriers of Using English Pop Songs for Vocabulary Acquisition among EFL Students - Putri, Aulia; Prasetyo, Yudy; Aisyah, Siti (Journey: Journal of English Language and Pedagogy, 2026)
This research aimed to examine the perception and challenges of students to learn vocabulary through English pop songs. This study used a qualitative descriptive method using a sample of 8 students in the 7 semester of the English Education Study Program at PGRI Delta University which were collected by means of semi-structured interviews and analyzed by mapping respondents' answers on several themes. Research indicated that students who found English pop songs to be a fun and motivating medium because they could acquire vocabulary using lyrical repetition, but there were also some challenges such as fast tempo of songs with unclear pronunciation, unfamiliar accents that used slang and metaphor and distractions due to focusing more on music than words. It could be concluded that pop songs in English were a solution in learning vocabulary, but lecturers or teachers needed to guide appropriately and choose songs selectively so that they could be used optimally and minimize obstacles.